2022
DOI: 10.1007/s10902-022-00606-2
|View full text |Cite
|
Sign up to set email alerts
|

Can Environmental Protection Behavior Enhance Farmers' Subjective Well-Being?

Abstract: The significance of environmental protection activities is well known, but little literature has focused on the well-being effects of environmental protection behavior among farmer groups. This study provides new literature support for farmers and rural development issues. Using data from the 2013 China Integrated Social Survey, a systematic and robust examination of the happiness effects of environmental protection behavior among Chinese farmers and their transmission mechanisms was conducted with the help of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Generally speaking, well-being can be divided into two dimensions: subjective and objective. The subjective dimension emphasizes the subjective experience of well-being, while the objective dimension focuses on the objective reality of well-being ( Qi et al, 2023 ). Compared with objective dimensions, SWB has attracted extensive attention in the academic community due to its greater inclusiveness.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Generally speaking, well-being can be divided into two dimensions: subjective and objective. The subjective dimension emphasizes the subjective experience of well-being, while the objective dimension focuses on the objective reality of well-being ( Qi et al, 2023 ). Compared with objective dimensions, SWB has attracted extensive attention in the academic community due to its greater inclusiveness.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…But overall speaking, it is 'reliable, valid, and viable' in survey-based studies (Abdel-Khalek, 2006, p.129). The singleitem measurement for well-being has been adopted in a series of analyses based on the CGSS (e.g., Ding et al, 2021;Qi et al, 2023); most recently, Yan et al (2023) reported that the single question on well-being from the 2017 CGSS is 'reliable and effective' (p. 4) in the Chinese context.…”
Section: Dependent Variablementioning
confidence: 99%
“…The two studies illustrated below, which discussed the 'seldom'-explored linkage between language and well-being (Zhang et al, 2021, p. 2), were highly relevant to our study hence they represented our 'major' considerations. There are many examples in social science disciplines other than language-related fields; for instance, the 2013 CGSS data were the focus of Qi et al (2023); Yan et al (2023) utilised the 2017 CGSS data, claiming that this wave provided 'the most recent data from the CGSS' (p. 4, emphasis added).…”
Section: Analytic Strategymentioning
confidence: 99%
“…Notwithstanding the considerable research on garbage classification, previous studies have not explored the association between garbage classification and people's subjective well-being. One exception is Qi et al (2022), who documented that environment protection behaviour (e.g., garbage classification and donating money for environmental protection) can enhance farmers' subjective well-being in China. However, they only considered garbage classification as an element of the synthesized key explanatory variable (i.e., environmental protection behaviour), shedding no light on the association between garbage classification and subjective well-being.…”
Section: Introductionmentioning
confidence: 99%